The active participation of elderly patients in traditional Chinese medicine consultations as means to creating a community of practice: A case study in Hong Kong - Pun, Jack (Frontiers in Psychology, 2022)
Despite its historic role in Chinese society and its popularity with an elderly Chinese population, limited research has explored the discursive practices of Traditional Chinese Medicine (TCM). Our analysis of practitioner–patient interactions illustrated the reasons why TCM is widely welcomed by a specific patient group. This paper adopted the concept of Community of Practice (CoP) as a theoretical framework to document how patients interact with TCM practitioners to construct meaning through a process of participation and reification. This study aimed to explore how patients in a medical consultation context developed an understanding of their conditions and how they strategically used medical terminology to enact meaningful exchanges to realise their CoP. An inductive qualitative discourse analysis was conducted to for nine elderly patients (i.e., age > 65) in Hong Kong to demonstrate the role that a CoP played in a joint process of knowledge construction to promote a patient-centred practice and foster the active participation of the patients. TCM practitioners can develop specific communication skills to promote their patients’ CoP, which will improve patient-centred care, empower patients to actively engage in their treatments and result in higher levels of patient satisfaction.